DEPRESSION AMONG NURSING STUDENTS IN INDONESIA: PREVALENCE AND ASSOCIATIONS WITH AGE AND LEVEL OF NURSING EDUCATION: NATIONAL SURVEY - Dian Sari (Jurnal Kesehatan Kusuma Husada, 2026)
Background: Depression is more prevalent among nursing students than in the general student population, largely due to academic demands and the pressures of clinical practice. In Indonesia, evidence on demographic factors associated with depression among nursing students, such as age and level of nursing education, remains limited. This study aimed to examine the associations between age and educational level and the occurrence of depression among nursing students in Indonesia.Methods: A cross-sectional study was conducted with 690 nursing students recruited from 30 provinces across Indonesia. Participants were selected using convenience and snowball sampling. Data were collected via an online questionnaire that included demographic characteristics and the Beck Depression Inventory (BDI), Indonesian version.Results: The findings revealed that 21.01% of nursing students experienced depressive symptoms. The mean age of the respondents was 21 years old, and the majority were enrolled in a Bachelor’s degree program in Nursing (61.5%). Statistical analysis indicated no significant association between age and depression status (p = 0.611), and a significant association was identified between educational level and depression (p = 0.023), with students enrolled in the regular Bachelor of Nursing program demonstrating a higher prevalence of depression.Conclusion: Depression remains a significant mental health problem among nursing students in Indonesia. Age was not associated with depressive symptoms, but education level emerged as a factor associated with depression. These findings highlight the need for increased psychological support and education-specific intervention strategies to prevent and reduce depression among nursing students.